Pelatihan Pendekatan Value Clarification Technique Model Matriks dalam Pembelajaran PKn-IPS bagi Guru SD Kecamatan Talawi Sawahlunto - Reinita Reinita (Pedagogi: Jurnal Ilmu Pendidikan, 2017)
The Value Clarification Technique (VCT) approach can foster a student’s awareness of critical thinking ​​through clarification and test the truth of values. In practice of learning sometimes teachers ignore the guidance of attitudes and character values. This is caused by the lack of teacher’s skills to implement the ​​learning approach in learning Civics and Social Science. So that impact on low student character and student unready to face competition globally. The purposes of this training are to increase insight and train teachers in Talawi to apply VCT approach model matrix in Civics and Social Science lesson, in order to improve the student’s character. The targets are elementary school teachers in Talawi (20 people). The method in this training consists of the Lecture Method, Question and Answer, Discussions, used to describe the material, encouraging active participation of teachers, selecting material to be designed with steps of the VCT model matrix. Recitation Method for training teachers in designing RPP with the VCT matrix. Simulation Method to train teachers to implement Civics and Social Science learning with the VCT model matrix. The results are teachers in Talawi can understand, design-implement, improve their skills in implementing Civics and Social Science with VCT matrix model that can influence the improvement of student’s character values.